2016
DOI: 10.1080/01496395.2016.1177075
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption separation of raffinose from sucrose by activated carbon: Equilibrium, kinetics and dynamic breakthrough

Abstract: Separation of oligosaccharides with a varied number of monosaccharides is an important issue in the food chemistry. Raffinose, a functional oligosaccharide, has attracted increasing attentions due to its strong proliferative effect on bacteria. Industrially, cottonseed meal is an important resource for producing raffinose; however, raffinose extracted from the cottonseed meal contains a significant amount of sucrose that debases the raffinose's quality. In this work, an adsorptive separation of raffinose and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…is belong to Meliponini (Family of Apidae) are also called "stingless bees' '. Meliponini is closely related to the honey bees, Apini, both belong to the family of Apidae [21]. Trigona spp.…”
Section: Characterization Of Honey Oligosaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…is belong to Meliponini (Family of Apidae) are also called "stingless bees' '. Meliponini is closely related to the honey bees, Apini, both belong to the family of Apidae [21]. Trigona spp.…”
Section: Characterization Of Honey Oligosaccharidesmentioning
confidence: 99%
“…Beside, it is a high availability adsorbent, which is widely used and affordable. Bao et al [21] showed that the adsorption power of activated carbon on raffinose (0.60~0.65 g/g) was higher than that on sucrose (0.35~0.40 g/g). Raffinose is an oligosaccharide compound.…”
Section: Characterization Of Honey Oligosaccharidesmentioning
confidence: 99%
“…The application of a column packed with AC has been applied in the manufacture of fructose syrup. 13 The intricate pores of AC provide a long enough route for the saccharide separation; meanwhile, the surface functional groups contribute to the formation of diverse affinities between AC and different saccharides. 14 Besides pore structure and surface functional groups, another concern for AC column separation is the flow velocity.…”
Section: ■ Introductionmentioning
confidence: 99%